1994
DOI: 10.1016/0735-1097(94)90307-7
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular outflow reconstruction with cryopreserved homografts in pediatric patients: Intermediate-term follow-up with serial echocardiographic assessment

Abstract: Cryopreserved homograft dysfunction is frequent and progressive. Young age at operation (< 18 months) predicts more rapid deterioration. Doppler echocardiography is reliable in assessing the systolic gradients across homografts. Serial echocardiographic assessment in the follow-up of these patients accurately characterizes these problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 13 publications
1
32
0
Order By: Relevance
“…Freedom from re-operation or explants of the valves in our series was greater than 95% at 5 years and compare very favorably to large scale studies looking at cryopreserved valved allografts [15], bovine jugular venous valved conduits [16,17] or stented porcine or pericardial valves [18,19] where an 80-85% freedom from explantation or reintervention at 5 years can be expected. These valves also rarely showed evidence of even mild insufficiency and compare favorably with cryopreserved allografts, where some insufficiency is common and moderate insufficiency occurs about 15-25% of the time in the intermediate-term [20,21]. Because of this excellent intermediate-term ability to remain competent (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…Freedom from re-operation or explants of the valves in our series was greater than 95% at 5 years and compare very favorably to large scale studies looking at cryopreserved valved allografts [15], bovine jugular venous valved conduits [16,17] or stented porcine or pericardial valves [18,19] where an 80-85% freedom from explantation or reintervention at 5 years can be expected. These valves also rarely showed evidence of even mild insufficiency and compare favorably with cryopreserved allografts, where some insufficiency is common and moderate insufficiency occurs about 15-25% of the time in the intermediate-term [20,21]. Because of this excellent intermediate-term ability to remain competent (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…23 Intermediate-term echocardiographic follow-up of pediatric patients who underwent RVOT reconstruction with cryopreserved homografts reported by Chan et al revealed progression of homograft regurgitation Ͼ2 grades in 35% of the patients, as well as progression of homograft stenosis with gradient Ͼ25 mm Hg in 51% of implanted homografts. 24 These phenomenon may be related to early postoperative inflammatory reaction to the pulmonary homograft that leads to extrinsic compression and/or shrinkage or immunologic homograft valve deterioration. 25 None of these complications were observed in our patients; during the entire follow-up period there were no signs of graft stenosis, valve degeneration, progression of valve regurgitation, cusp thickness, or reduction of cusp's mobility.…”
Section: Discussionmentioning
confidence: 99%
“…PR has been another concern with the valved conduit [22]. In our study, although the tri-leaflet conduits obviously functioned satisfactorily in the early postoperative phase, PR is ultimately inevitable.…”
Section: Discussionmentioning
confidence: 89%